PENGEMBANGAN LEMBAR KEGIATAN SISWA (LKS) BERBASIS KONSTRUKTIVIS UNTUK MELATIHKAN KETRAMPILAN PROSES SAINS - Supiati, Anis (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
Appropriate with constructivist principles, a child learn if they actively construct knowledge in their brain. One way to implement in the classroom is a way to package learning materials in the form of worksheets. The purpose of the research is to develop a constructivist-based worksheets to practice science process skills that feasiable theoretically and empirically. Types of research, namely the development of a customized worksheets with 4-D development procedures. The research instrument used in the form of sheet validation worksheets and student activity sheets. Data were analyzed by descriptive quantitative. The results showed that, LKS has developed theoretically feasible and get a percentage of 97.47% with a very decent criteria. Percentage of students meeting Activity 1 and 2 get a percentage of 82.4% and 87.5%. Keywords: constructivist-based worksheets, science process skills